An Integrated Investment Scheduling Model for New Job Shops: A Phase-In Approach - Idris, Musibaudeen Olatunde; Adeboye, Busayo Sunday; Yusuf, Fatai Abolore; Adekanye, Selimat Aderike (Universitas Muhammadiyah Magelang, 2022)
The establishment and sustainability of the small-scale manufacturing sector is a great contributor to any nation's economic and technological development. A job shop is a typical small-scale manufacturing system that produces simple equipment and machine parts as well as technical services in developing nations. This type of manufacturing system requires versatile production machines for its activities. This requires enormous capital that most interested investors could not afford, and a majority of the commercial banks are not willing to provide financial assistance. This study develops a model using the theory of internal funding by employing the little initial capital in phasing- in the acquisition of the needed machinery, construction of factory space in modular forms, and adequate consideration for recurrent expenditure (i.e. working capital). The initial capital is periodically augmented from the ploughed-back earnings for the gradual acquisition of other machinery until a fully functional job shop emanates within the shortest possible time. Job shop general scheduling methods available in the literature could not be employed to solve the model developed in this study due to its peculiarities. Hence a special heuristic that employs suitable decision rules was formulated and solved using software developed for the purpose. The model developed in this study will be helpful to the investors in job shops, especially in developing nations, to overcome the problem of financing the venture.